Working Late: Exploring the Workplaces, Motivations, and Barriers of Working Seniors - Vivian W. Mott Ph.D. (Adult Education Research Conference, 2006)
This phenomenological research explored the nature of seniors’ employment. Findings focused on seniors’ motivations for continuing employment, barriers and coping mechanisms, generational differences, the role of self-directed learning, and the effect of age, status, and experience on security and capital in the workplace.
Keywords: Older workers; Workplace; Motivations; Barriers; Phenomenological